Butterfly bones - Gowans, Elisabeth (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2012)
Butterfly Bones is a lyrical sequence of poetry and prose poems organised to trace a rhythmical, emotional pattern of experience. In its subject matter, the sequence presents an implied personal narrative recording the author's grief in the ten months following her mother's death in January 2011. It presents brief, vivid scenes from the poet's daily life in a rural village outside Grahamstown, and observations of creatures and her natural surroundings, which serve as a counterpoint to her grief. It can also be read as a meditation on writing, solitude and the possibilities of poetry.
Keywords: Uncatalogued